Cooperative Co-evolution using The Brain Storm Optimization Algorithm - El-Abd, Mohammed (2016)
The Brain Storm Optimization (BSO) algorithm is a powerful optimization approach that has been proposed in the past few years. A number of improvements have been previously proposed for BSO with successful application for real-world problems. In this paper, the implementation of a Cooperative Co-evolutionary BSO (CCBSO) algorithm that is based on the explicit space decomposition approach is investigated. The improved performance of CCBSO is illustrated based on experimental comparisons with other BSO variants on a library of 20 well-known classical benchmark functions.